Karakterisasi Ekstrak Air Daun Dewa (Gynura pseudochina (L.) DC Dan Penetapan Kadar Flavonoid Totalnya - Harrizul Rivai; Femiwati Femiwati; Krisyanella Krisyanella (STIFARM Padang, 2011)
The study about characterization of water extract of Gynura pseudochina (L.) DC leaves has been done. The study reveals the following non-spesific and specific parameters. It’s water content, density, total ash, insoluble acid ash are 78.69 + 0.21 %; 1.08 + 0.0 %; 3.99 + 0.12%; and 0.67 + 0.10% respectively. It’s bacterial count are 4.4 x 103 colonies/g and 2.3 x 102 colonies/g for fungis count. Gynura pseudochina (L.) DC also known as daun dewa in Indonesia. It has Gynura pseudochina Folium Aqueous Liquidum Extractum as it’s identity. The extract is a liquid extract, with swarthy brown colored, specific smells and tasteless. It’s contains secondary metabolites such as alkaloids, flavonoids, saponins and tannins. The content of compounds soluble in water are 20.25 + 0.53% and soluble in ethanol are 8.59 + 0.79%. The total flavonoids content obtained using spectrophotometry UV-Visible method was 0.07 + 0.01 % w/w.